Phosphorus–nitrogen compounds. Part 64. Comparative reactions of spiro and ansa (N/O) cyclotetraphosphazenes with bulky (4-fluorobenzyl) N/N and N/O donor type bidentate reagents: structure, stereogenic properties and cytotoxic activity studies. (4th August 2022) - Elmas, Gamze; Binici, Arzu; Yakut, Mehtap; Okumuş, Aytuğ; Kılıç, Zeynel; Çoşut, Bünyemin; Hökelek, Tuncer; Çerçi, Nebahat Aytuna; Açık, Leyla
Abstract : Novel inorganic–organic hybrid multiheterocyclic-spiro and ansa cyclotetraphosphazenes were synthesized. The spectral, crystallographic, and stereogenic properties, and the cytotoxic activities of the compounds were presented. Abstract : The reaction of octachlorocyclotetraphosphazene, N4 P4 Cl8 (1 ) (OCCP, tetramer), with an equimolar amount of sodium 3-( N -ferrocenylmethylamino)-1-propanoxide (L1 ) resulted in the formation of ferrocenyl-spiro-(2 ) and ferrocenyl-2- cis -4-dichloro-ansa-(3 ) cyclotetraphosphazenes. Both of the starting compounds were used to produce the new inorganic–organic hybrid multiheterocyclic-spiro and ansa cyclotetraphosphazenes. Spiro (2 ) was treated with excess N -(4-fluorobenzyl)- N ′-ethyl-1, 2-diaminoethane (L2 ) to give 2- trans -6-dispiro ( trans -2a ) and 2- trans -4- cis -6- trans -8-tetraspiro ( tetraspiro -2a ) cyclotetraphosphazenes. Spiro (2 ) was also reacted with excess sodium 3-(4-fluorobenzylamino)-1-propanoxide (L3 ) to produce 2- trans -6-dispiro ( trans -2b ), 2- cis -6-dispiro ( cis -2b ), 2- cis -4- trans -6-trispiro ( trans -2c ), 2- cis -4- cis -6-trispiro ( cis -2c ), 2- cis -4-dichloro-ansa-4- trans -6-spiro(N/O) ( ansa -2b ) and 2- cis -4-dichloro-ansa-6- trans -8-dispiro(N/O) ( ansa -2c ). The reactions of 2, 4-ansa (3 ) with excess L2 led to the formation of 2- cis -4-dichloro-ansa-2- trans -6-spiro(N/N) ( trans -3a ) and 2- cis -4-dichloro-ansa-2- cis -6-spiro(N/N) ( cis -3a ) cyclotetraphosphazenes. However, the reactions of 2, 4-ansa (3 ) with excess L3 afforded monospiro 2- cis -4-dichloro-ansa-4- trans -6-spiro(N/O) ( trans -3b ) and 2- cis -4-dichloro-ansa-4- cis -6-spiro(N/O) ( cis -3b ) and dispiro 2- cis -4-dichloro-ansa-6- trans -8-dispiro(N/O) ( trans -3c ) and 2- cis -4-dichloro-ansa-6- cis -8-dispiro(N/O) ( cis -3c ). The obtained products were characterized by spectroscopic techniques. The crystal structures of trans -2b and cis -3b were clarified by single crystal X-ray analysis. The products had stereogenic P-centres except for trans -2a, tetraspiro -2a, trans -2b and cis -2b . The stereogenic properties of tetrameric phosphazenes were evaluated by X-ray crystallography and chiral high performance liquid chromatography (HPLC) methods. The structure of cis -3b revealed the absolute configurations of the enantiomers ( SS ′ R ′′/ RR ′ S ′′). The broad HPLC peak of cis -3b indicates that it may exist as a resamate in solution. The cytotoxic activities of the cyclotetraphosphazenes were evaluated using an MTT assay against L929 mouse fibroblasts, A549 non-small lung cancer and Caco-2 colorectal adenocarcinoma cells. Compound cis -3b was found to be very effective in all cell lines up to 104.1 μM.